2018
DOI: 10.1186/s13756-018-0417-y
|View full text |Cite
|
Sign up to set email alerts
|

High frequency and molecular epidemiology of metallo-β-lactamase-producing gram-negative bacilli in a tertiary care hospital in Lahore, Pakistan

Abstract: BackgroundMetallo-β-lactamase (MBL)-producing isolates have a strong impact on diagnostic and therapeutic decisions. A high frequency of MBL-producing gram-negative bacilli has been reported worldwide. The current study was based on determining the incidence of MBL-producing imipenem-resistant clinical isolates and investigating the β-lactamase gene variants in strains conferring resistance to a carbapenem drug (imipenem).MethodsA total of 924 gram negative isolates were recovered from a tertiary care hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 50 publications
4
31
1
Order By: Relevance
“…The DNA used for multiplex-PCR was extracted by the heat lysis method [16]. In Multiplex-PCR, 2 μl whole cell lysate DNA for each isolate was used separately in 25 μl PCR-master mix and amplification primers as previously mentioned [16, 28, 29]. PCR amplification conditions were: Initial step of denaturation at 95°C for 5 min followed by 35 cycles of denaturation at 95°C for 1 min then annealing at 56°C for 1.5 min, extension at 95°C for 1 min and the final extension was done at 95°C for 10 min (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The DNA used for multiplex-PCR was extracted by the heat lysis method [16]. In Multiplex-PCR, 2 μl whole cell lysate DNA for each isolate was used separately in 25 μl PCR-master mix and amplification primers as previously mentioned [16, 28, 29]. PCR amplification conditions were: Initial step of denaturation at 95°C for 5 min followed by 35 cycles of denaturation at 95°C for 1 min then annealing at 56°C for 1.5 min, extension at 95°C for 1 min and the final extension was done at 95°C for 10 min (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…This variation may be associated with different factors like availability and use of antibiotics, difference of nosocomial and community-based studies, and methods to determine the MBL-producers [15,16,31]. The studies that have employed molecular methods to determine the gene variants have also reported the co-existence of other beta-lactamase genes with MBL related genes [12,32,33]. This aspect of the study is in concordance with reports from different regions of the world where the simultaneous presence of other betalactam genes with metallo β-lactamase genes have been described [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the studies included here have also reported the serine betalactamases, OXA variants, and KPCs to be the causative agents of carbapenem resistance. [12,38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NDM-1, 2, 3, 4 [14][15][16]) and the genes encoding them (bla NDM-1, 2, 3 ). Bacterial strains which are positive for bla NDM (genotypic resistance marker gene) and also produce NDM enzymes are particularly dangerous because, (1) There is no routine standard phenotypic test for MBL detection; (2) Consequently there is a possibility of high prevalence of unrecognized asymptomatic carriers amongst general population; (3) There is lack of effective antibiotics against NDM-1-positive superbugs; and (4) Plasmids from these bacteria can undergo wide rearrangement and thus can cause widespread horizontal transmission of the antibiotic resistance gene (bla NDM-1 ) [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%